Exploring the Relationship between Online Customer Engagement on Luxury Fashion Brands - Senevirathne, Asheni Thiwanka; Premachandra, Nimasha Madhushani; Budiharseno, Rianmahardhika Sahid (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Social media creates an environment for marketers to connect with target customers in a personalized and interactive manner. It also indicates social media interaction, engagement, and personal communication have become an essential brand communication channel for fashion brands. It is also a key marketing tool for brand equity, brand loyalty and brand preference. Among social media, Instagram is the most important platform for communication and marketing for the luxury fashion industry. This study examines how Louis Vuitton, a luxury fashion brand, engages with their customers on Instagram. While exploring the literature very few researches have been conducted on the relationship between online consumer engagement on the popular social media platform Instagram and luxury fashion brand Louis Vuitton. The objectives of this research are to clarify the concept of luxury brands, to analyze how these brands utilize Instagram for enhancing consumer engagement through content strategies and audience interactions, and to evaluate the effectiveness of influencer and celebrity endorsements in shaping brand image and influencing consumer behavior. Using Thematic Analysis and Sentiment Analysis, the study reveals that social media significantly contributes to brand equity. Engaging content and high levels of interaction foster an emotional connection between consumers and brands, leading to increased loyalty and purchase intent. By considering the research implications and recommendations for future exploration, stakeholders such as marketers, and academics can gain valuable knowledge. Marketers can optimize and develop effective social media strategies aimed at enhancing brand equity and shaping consumer behavior. Academics can expand the body of knowledge on social media’s influence on consumer behavior.